For the following values of a, b and c, verify that (a × b ) × c = a × (b × c)
a = 1/3 ,
b = −3/4 ,
c = 1/3
Answers
Answered by
1
refer to the image for solution hope it will help you
if it helped you then help me by subscribing my channel maths made easy mme for enjoying maths with easy learning
Attachments:
![](https://hi-static.z-dn.net/files/d7e/23c74b137a664e0ae1ee3c3d9882799e.jpg)
![](https://hi-static.z-dn.net/files/dce/c24c7acb35311e2958238c48e8ac290c.jpg)
Answered by
1
Step-by-step explanation:
by simply putting the value
(1/3×-3/4)×1/3=1/3×(-3/4×1/3)
4-9/12×1/3=1/3×-9+4/12
-5/12×1/3=1/3×-5/12
-15+12/36=+2-15/36
-3/36= -3/36
1/12=1/12
Similar questions